Terveydenhuollon vaaratapahtumien hallinta - Lehesvuo, Riikka; Jalonen, Harri (Hallinnon tutkimuksen seura, 2022)
Patient safety incident management in healthcare Managing patient safety incidents (adverse events and near-misses) is a key part of healthcare management, but research on the subject is fragmented. This article conducts a scoping review to examine the management of patient safety incidents. The purpose of the review was to unveil the process of managing patient safety incidents, its antecedents, and the agents involved. The review suggests that managing patient safety incidents consists of three interdependent segments in which management is proactive (before the unexpected event), concurrent (during the unexpected event), or reactive (after the unexpected event). The key agents were individuals and groups working in healthcare. Management and organizational culture play a significant role in the success of a holistic system of patient safety incident management.
Keywords: patient safety incident; patient safety management; scoping review; fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|